Citrus Pest Quick Guide: California Red Scale (Aonidiella aurantii) - X. Martini; J. Price (EDIS)
This factsheet gives the general public and citrus growers basic knowledge regarding the California red scale. Written by X. Martini and J. Price, and published by the UF/IFAS Entomology and Nematology Department, November 2022.